Physicochemical Parameters and Heavy Metals Levels in Water from Boreholes and Hand-dug Wells from Selected Communities in Kuje Area Council, Federal Capital Territory, Abuja, Nigeria - H. A. Ari; B. O. Ekute (Journal of Applied Sciences and Environmental Management)
Access to potable clean water is essential in promoting good health of man. Consequently, the objective of this research was to evaluate the physicochemical parameters and levels of Zn, Cr, Cd, Fe, Pb, Mn, and Ni in water from boreholes and hand-dug wells from selected communities in Kuje Area Council, Federal Capital Territory, Abuja, Nigeria. The physicochemical parameters were determined using appropriate standard methods, and heavy metals were analysed using AAS after wet digestion with Aqua regia. All analysis were done in triplicates. Data obtained show that the mean level of physicochemical parameters in all the boreholes except for alkalinity were significantly different from the values observed for the wells at p≤0.05. The values recorded for most of the water samples for all the parameters and heavy metals were within WHO permissible limits. Nitrate levels was also high in the hand-dug wells. The Fe and Mn mean levels were higher than other elements analysed, and were above permissible limits in most of the boreholes. A survey on the perception of the residents of KAC indicated 57.06% of the populace having skin irritation, water related sicknesses, coloration of storage vessels and deposition of dark coloured sediments which could be due to Mn and Fe levels in the water source. Generally, the water sources are suitable for domestic use and could be made fit for drinking after certain treatment to reduce the levels of nitrate, Fe and Mn in the affected communities.